2020
DOI: 10.14453/aabfj.v14i1.9
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating Role of Corporate Social Responsibility (CSR) Disclosure on Good Corporate Governance (GCG) and Firm Value. A Technical Note

Abstract: The application of Good Corporate Governance (GCG) and Corporate Social Responsibility (CSR) disclosure is one way to increase company value by focusing on the balance of internal and external interests. This study aim is to determine the effect of GCG and CSR disclosure on company value. This type of research is explanatory research with a quantitative approach, using a sample of 13 mining companies listed on the Indonesia Stock Exchange. By using Partial Least Square (PLS) technique, the result showed that (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0
11

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 1 publication
(1 reference statement)
3
41
0
11
Order By: Relevance
“…Beberapa penelitian di beberapa negara menunjukkan bahwa corporate governance berpengaruh positif dan signifikan terhadap Nilai Perusaan (Budiharjo, 2020;Worokinasih & Zaini, 2020;Nisasmara & Musdholifah, 2016;Balachandran & Faff, 2015;Mukhtaruddin et al, 2014;Siahaan, 2013;Ammann et al, 2011;Carter et al, 2003;Erhard et al, 2003). Sedangkan penelitian Abbasi et.…”
Section: Issn (Print): 2598-7763 Issn (Online): 2598-7771unclassified
“…Beberapa penelitian di beberapa negara menunjukkan bahwa corporate governance berpengaruh positif dan signifikan terhadap Nilai Perusaan (Budiharjo, 2020;Worokinasih & Zaini, 2020;Nisasmara & Musdholifah, 2016;Balachandran & Faff, 2015;Mukhtaruddin et al, 2014;Siahaan, 2013;Ammann et al, 2011;Carter et al, 2003;Erhard et al, 2003). Sedangkan penelitian Abbasi et.…”
Section: Issn (Print): 2598-7763 Issn (Online): 2598-7771unclassified
“…They concluded that the more accurate or timely reported earnings reflect shocks in the present value of expected future dividends, the higher the earnings quality. Therefore, earnings quality is defined by researchers using certain earnings qualities such as persistence or sustainability, predictive ability, smoothness, conservatism, value-relevance, timeliness, earnings management or earnings manipulation, and accrual quality (Hassan et al, 2020;Uemura, 2020;Lestari & Hanifah, 2020;Worokinasih & Zaini 2020). Many scholars and researchers agree, however, that earnings that are truly deemed of high unprecedented quality are those with a high level of persistence, predictability, reduced volatility, timing, lower level of earnings management, and higher accrual quality (Khairul & Wan 2014).…”
Section: The Concept Of Earning Qualitymentioning
confidence: 99%
“…Companies should also form a Board of Directors with the appropriate size, financial and accounting expertise, and female board members. Worokinasih and Zaini (2020) investigated the mediating effect of corporate social responsibility disclosure on good corporate governance and firm value using a sample of 13 mining companies listed on the Indonesia Stock Exchange. By using the Partial Least Square (PLS) technique, the result showed that good corporate governance has a significant and positive effect on corporate value and corporate social responsibility does not significantly mediate the relationship between good corporate governance and firm value.…”
Section: Review Of Related Empirical Literaturementioning
confidence: 99%
“…Oleh karena itu perusahaan belum dapat memberikan manfaat secara maksimal terhadap para stakeholder. Hasil penelitian ini mendukung penelitian (Worokinasih & Zaini, 2020) dan (Putri et al, 2016).…”
Section: Tabel 4 Hasil Analisis Regresi Moderasi (Mra)unclassified